DOI: 10.31274/rtd-180813-15333
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of lactating dairy cows to exogenous glucagon

Abstract: Introduction Materials and Methods Results Discussion Conclusion Ac kn ow 1 ed gmen t s References POTENTIAL TREATMENT OF FATTY LIVER WITH 14-DAY SUBCUTANEOUS INJECTIONS OF GLUCAGON Abstract Introduction Materials and Methods Results Discussion Conclusion Acknowledgments References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 293 publications
(316 reference statements)
3
14
1
Order By: Relevance
“…Furthermore, decreased concentrations of HDL 1 -phospholipids (Figure 4) and HDL 2 -free cholesterol (Figure 7) were limited to prolonged periods of elevated ambient temperatures (Figures 5 and 8). Another indication of minimal or no detrimental effects on health and performance is that neither milk production, health status, nor reproductive performance was decreased in cows that were injected with glucagon (Bobe, 2002;Bobe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, decreased concentrations of HDL 1 -phospholipids (Figure 4) and HDL 2 -free cholesterol (Figure 7) were limited to prolonged periods of elevated ambient temperatures (Figures 5 and 8). Another indication of minimal or no detrimental effects on health and performance is that neither milk production, health status, nor reproductive performance was decreased in cows that were injected with glucagon (Bobe, 2002;Bobe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In companion reports, it has been demonstrated that subcutaneous injections of glucagon at 15 mg/d for 14 d beginning at d 8 postpartum decreased concentrations of liver TAG in multiparous cows older than 3.5 yr (Bobe et al, 2003) and had beneficial effects on health and reproductive performance (Bobe, 2002). In monogastric species, glucagon decreases concentrations of plasma lipoprotein components because glucagon shifts the use of NEFA in hepatocytes from synthesis of TAG and other lipids to oxidation and ketogenesis of NEFA (McGarry and Foster, 1980;Witters and Trasko, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty liver (i. e., hepatic lipidosis) is one of the major metabolic disorders of dairy cows in the peripartal period, which affects up to 50% of cows in early lactation (Jorritsma et al, 2001). Fatty liver can negatively affect the productivity, health status, and reproductive performance of high-producing dairy cows (Herdt, 1988;Veenhuizen et al, 1991;Wensing et al, 1997;Bobe, 2002) and can be treated with continuous, intravenous infusions of glucagon for 14 d (Hippen et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of exogenous glucagon increases concentrations of plasma glucagon, glucose, and insulin in lactating dairy cows (de Boer et al, 1986;Trevisi et al, 1997;Hippen et al, 1999b;She et al, 1999) by stimulating hepatic gluconeogenesis, glycogenolysis, amino acid uptake, and ureagenesis (Flakoll et al, 1994;Donkin and Armentano, 1995). The metabolic response to glucagon depends on the dosage and the age, stage of lactation, and health of cows, with weaker responses at lower glucagon dosages in older, ketotic cows in early lactation (de Boer et al, 1986;Holtenius and Trå vén, 1990;Holtenius and Holtenius, 1996;Steen et al, 1997;Hippen et al, 1999aHippen et al, , 1999bShe et al, 1999;Bobe, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation